Advances in preparation, analysis and biological activities of single chitooligosaccharides. (30th March 2016) - Li, Kecheng; Xing, Ronge; Liu, Song; Li, Pengcheng
Highlights: Both separation and synthesis methods for single COS preparation are summarized. An overview of techniques to analyze well-defined COS is provided. Recent progress in diverse bioactivities of COS of defined size is presented. Abstract: Chitooligosaccharides (COS), as a source of potential bioactive material, has been reported to possess diverse bioactivities. These bioactivities of COS are often tested using relatively poorly characterized oligomer mixtures during past few decades, resulting in difficult identification of COS molecules responsible for biological effects. Therefore, a new interest has recently been emerged on highly purified COS of defined size. Several technological approaches have been used to produce single COS and new improvements were introduced to their characterization in order to understand the unrevealed structure-function relationship. Here we provide an overview of techniques that were used to prepare and analyze reasonably well-defined COS fractions. Based on the latest reports, several applications of single COS for plants and animals, are also presented, including antitumor, immunostimulatory, antioxidant, antimicrobial, elicitors of plant defence and neural activity.